2021
DOI: 10.3389/fpsyg.2021.709853
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Reminiscence Therapy on Alleviating Depressive Symptoms in Older Adults: A Systematic Review

Abstract: Objective: Depression is one of the most common problems faced by older adults. Reminiscence therapy, defined as using the recall of past events, feelings, and thoughts facilitating pleasure, is one type of psychotherapy that could alleviate depressive feelings among older adults, improve their quality of life, and help them live independently. Reminiscence therapy originated from geriatric psychiatry, and is an effective non-pharmacological intervention that could be structured or unstructured and be conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
6
29
0
2
Order By: Relevance
“…The results confirm the hypothesis that "group reminiscence therapy has an effect on decreasing depression level of elderly in nursing home. " This finding is consistent with the findings of pre-existing research and systematic rewiev studies on the efficacy of reminiscence therapies on the rate of depression in the elderly people (22,24,29,30).…”
Section: Discussionsupporting
confidence: 91%
“…The results confirm the hypothesis that "group reminiscence therapy has an effect on decreasing depression level of elderly in nursing home. " This finding is consistent with the findings of pre-existing research and systematic rewiev studies on the efficacy of reminiscence therapies on the rate of depression in the elderly people (22,24,29,30).…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis showed that the 12-week BLSB intervention resulted in a significant decrease in depression scores among the intervention group compared to the control group based on the GDS-15 depression scores. This result was consistent with several systematic reviews that reported a small to medium effect of BLSB in reducing depressive symptoms among the general older adult populations [8,16,17]. Depression has been considered a major health risk among the older adult population due to their increasing vulnerabilities to physical and mental decline.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that BLSB effectively promoted life satisfaction among nursing home residents. This finding was consistent with two reviews that reported a significant pooled effect favoring the reminiscence-based intervention over control [16,17]. In addition, Tam et al reported no differences in the BLSB effect on life satisfaction between the type of sessions (individual versus group) [17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Affirmative reminiscence therapy can improve the quality of life of the elderly. This therapy is a psychotherapy-based therapy by exploring pleasant memories; then, the memories serve to increase the self-esteem and self-satisfaction of the elderly which can further improve their quality of life of the elderly [8].…”
Section: Introductionmentioning
confidence: 99%